Investigating the pedagogical practices of grade 11 Mathematics teachers on the usage of interactive white boards: a case study of two Gauteng Township Secondary Schools - Montjane, Vincent Mahlaseletse (My University, 2018)
This research study is an investigation of the extent to which Interactive White Boards (IWBs) are pedagogically integrated in the classroom, and how they influence the pedagogic practices of teaching Mathematics. The use of IWB in education has transformed the culture of teaching and learning in the education system. However, the existence of IWB in the classroom has brought affordances and limitation, which affects the pedagogic practices of teachers daily. This case study has zoomed in to the Interaction Equivalency Theorem (Anderson, 2003) in trying to understand how IWB supports the three types of interaction: learner-content, learner teacher, and learner-learner. It is framed within the social structuralism and constructivist approach. The study sees learning as socially and actively constructed phenomenon and IWB as mediating artefacts in learning. The study was conducted in two Gauteng Province public secondary schools. Through questionnaires, interviews and observations data was generated from the participants. A qualitative approach was used to present, interpret and analyse data. The findings of the study indicated that the pedagogical affordances of IWBs has positively influenced the way Mathematics content is delivered, and has also given teachers pedagogic opportunities that support learner-content, learner-teacher and learner-learner interactions in the classroom.
A research report submitted in partial fulfilment of the requirements for the degree of Masters of Education to the School of Education, Faculty of Humanities, University of Witwatersrand, February 2018
Keywords: Interactive whiteboards; Mathematics--Study and teaching (Secondary)